Faktor-Faktor yang Mempengaruhi Struktur Modal pada Perusahaan Food And Beverage Di BEI - Mudiyana, Erica; Damayanti, Damayanti (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2023)
This study aims to prove the effect of profitability, liquidity, and company size on the capital structure of food and beverage companies listed on the Indonesia Stock Exchange . the sample for this research is a food and beverage company listed on the Indonesia Stock Exchange for the 2016-2021 period. Data obtained based on publication in financial repots accessed from the IDX’s official website (www.idx.co.id). The sample selection technique used was purposive sampling and research data were obtained for 14 companies for 6 (six) years, so the number of observations was 84. The data analysis method used was multiple linier regression analysis. The results of this study indicate that profitability has no significant negative effect, significant negative effect , and significant negative firm size. The estimation result of the regression test of determination show an adjusted R2 value of 0,295. This means that profitability , liquidity, and company size in this regression model are able to explain variations in debt policy of 29,5%, while 70,5% are explained by other factors not included in this research model.  Keywords: profitability, liquidity, company size and  capital structure.